Функционалистская парадигма Роберта Мертона в современном социологическом дискурсе - Кучеренко, В. (Социология: теория, методы, маркетинг, 2000)
R.Merton’s theoretical model of structural and functional analysis is one of the most influential models in contemporary social sciences. His ideas of analytical strategy and functional relations, the notions of manifest and latent functions, disfunction and anomie, the concept of “middle rang” theory and others are widely used nowadays in various sociological investigations. Merton’s theoretical lines are gaining new features in contemporary sociological discourse, in the context of postmodern approach to social reality in particular.